1994
DOI: 10.1149/1.2054745
|View full text |Cite
|
Sign up to set email alerts
|

Mass‐Transfer Behavior of Electrochemical Reactors Employing Vibrating Screen Electrodes

Abstract: This work concerns the use of vibrating screens as electrodes in building electrochemical reactors, i.e., (i) the effect of superimposed flow on the mass-transfer coefficient at vibrated screens; and (it) factors affecting the relation between the mass-transfer coefficient and mechanical power consumed in vibrating the screen electrode. Superimposed solution flow using superficial velocity in the range of 0.7 to 5.4 cm/s enhanced the mass-transfer coefficient at relatively low vibration intensities, and at hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 3 publications
2
6
0
Order By: Relevance
“…The slight decrease in the mass-transfer coefficient observed when the velocity of the superimposed solution is increased in the turbulent flow regime may be ascribed to the fact that the superimposed upward flowing solution counteracts and weakens the downward flow induced by the upward stroke of the oscillating bed. A similar finding was observed by Sedahmed et al, who studied the effect of axial superimposed flow on the rate of mass transfer at an oscillating horizontal screen. Sung et al, who studied the rates of mass transfer from the horizontal cylinder in pulsating flow, found that the effect of pulsation on Sh decreases with an increase in the velocity of superimposed flow.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The slight decrease in the mass-transfer coefficient observed when the velocity of the superimposed solution is increased in the turbulent flow regime may be ascribed to the fact that the superimposed upward flowing solution counteracts and weakens the downward flow induced by the upward stroke of the oscillating bed. A similar finding was observed by Sedahmed et al, who studied the effect of axial superimposed flow on the rate of mass transfer at an oscillating horizontal screen. Sung et al, who studied the rates of mass transfer from the horizontal cylinder in pulsating flow, found that the effect of pulsation on Sh decreases with an increase in the velocity of superimposed flow.…”
Section: Resultssupporting
confidence: 86%
“…A similar finding was observed by Sedahmed et al, 9 who studied the effect of axial superimposed flow on the rate of mass transfer at an oscillating horizontal screen. Sung et al, 20 who studied the rates of mass transfer from the horizontal cylinder in pulsating flow, found that the effect of pulsation on Sh decreases with an increase in the velocity of superimposed flow.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…
ecently there has been a growing interest in using woven metallic screens in building catalytic and electrochemical reactors used to R conduct liquid-solid diffusion controlled reactions, in view of both their high specific area and turbulence promoting ability. For the rational design and operation of such reactors, the mass transfer behaviour of screens under different hydrodynamic conditions such as forced convection (Cano and Bohm, 1977;Storck et al, 1979;Sioda, 1977; Sedahmed et al, ZOOO), gas sparging (Katkout et al, 1988;Zaki et al, 2001) two phase flow (Coppola et al, 1989;Zaki et al, 2000) and vibration (Sedahmed et al, 1994) has been studied. Natural convection arises in electrochemical reactors as a result of changing interfacial solution density at the electrodes, where processes such as metal deposition, metal dissolution and ionic migration change the interfacial solution composition and its density.
…”
mentioning
confidence: 99%
“…Recently, it was shown that more than 20-fold increase in the mass transfer rate could be achieved by vibrating vertical electrodes along their length [4]. Among its applications in that field are electrochemical processing, electroplating, metal recovery from bio-leaching solutions, and more recently manufacture of Printed Wiring Board where electroplating is re-emerging of as the preferred technology for producing "sub-micron multi-level metallization" in ultra large scale integration [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%